Analisis Pengaruh Sektor Pariwisata Terhadap Penyerapan Tenaga Kerja Di Kalimantan Selatan Tahun 2011-2021 - Syahrif, Airul; Rahmini, Noor; Rizali, H. (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2024)
An area's employment rate may be significantly boosted by the tourist industry. The amount of tourist visits and tourist items may be seen as one way to examine the tourism industry. Employment in South Kalimantan is the target of this research, which intends to examine the relationship between tourist visits and tourism items. This research makes use of secondary data, namely time series data beginning in 2011 and continuing through 2021. Employment, the quantity of tourist items, and the number of tourist visits are the factors used in this research. This study used route analysis multiple linear regression as its method of analysis. Research in South Kalimantan Province indicated that employment was significantly affected by both the quantity of tourist visits and the quantity of tourist items.